2022
DOI: 10.1111/codi.16240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of repeat faecal immunochemical testing in symptomatic patients attending primary care

Abstract: Aim:The faecal immunochemical test (FIT) for faecal haemoglobin (f-Hb) helps determine the risk of colorectal cancer (CRC) and has been integrated into symptomatic referral pathways. 'Safety netting' advice includes considering referral for persistent symptoms, but no published data exists on repeated FITs. We aimed to examine the prevalence of serial FITs in primary care and CRC risk in these patients.Method: A multicentre, retrospective, observational study was conducted of patients with two or more consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Furthermore, various studies have investigated the benefits of repeated FIT testing 22. For instance, a recent cohort study looking at 5761 patients concluded that a second negative test within 12 months of the first sample, in the context of ongoing clinical concern reliably rules out CRC 23. However, BSG/ACPGBI recommendations concluded that there is currently insufficient evidence to recommend the use of a repeat FIT to guide referrals in routine practice 8.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various studies have investigated the benefits of repeated FIT testing 22. For instance, a recent cohort study looking at 5761 patients concluded that a second negative test within 12 months of the first sample, in the context of ongoing clinical concern reliably rules out CRC 23. However, BSG/ACPGBI recommendations concluded that there is currently insufficient evidence to recommend the use of a repeat FIT to guide referrals in routine practice 8.…”
Section: Discussionmentioning
confidence: 99%
“…However, these tools have used different combinations across the full range of fHb results—it is unlikely that any marker will add to the value of high fHb (≥100 μg Hb/g faeces or similar). Reduction of missed CRC below any threshold for urgent referral, based on an FIT result alone or in combination with other markers, may be improved by repeat testing 24,25 . We have not included the repeat‐tested group in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of missed CRC below any threshold for urgent referral, based on an FIT result alone or in combination with other markers, may be improved by repeat testing. 24,25 We have not included the repeat-tested group in our analysis. Although further work is required to validate this approach the 'cost'-financial and otherwise of a missed CRC is much higher than that of a repeat FIT.…”
Section: Context Of What Is Already Knownmentioning
confidence: 99%
“…Sensitivity for CRC improves with a two FIT strategy where referral for bowel visualization is made when at least one FIT result is ≥10 μg Hb/g [27,28], although at the expense of a higher positivity. Further existing literature on repeat FIT strategies show two FIT results <10 μg Hb/g as an effective safety net for CRC [29,30]. However, a systematic review has concluded that the existing literature is conflicting and minimal [31].…”
Section: Ta B L Ementioning
confidence: 99%